Desain Kurikulum Berbasis Kearifan Lokal pada Era Kurikulum Merdeka di SMP Negeri 2 Karangjambu - Priyo Patmono; Didik Prasetyo; Ade Ruswatie (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Local wisdom-based curriculum design is a strategy to integrate local cultural values, knowledge, and practices into the educational process so that students are not uprooted from their socio-cultural roots amid globalization and the development of the Merdeka Curriculum. Local wisdom embodies the values of mutual cooperation, responsibility, simplicity, tolerance, and environmental awareness, which are relevant to character building and the Pancasila Student Profile. This article aims to examine the concept, philosophical, juridical, and sociocultural foundations of local wisdom-based curriculum design, explain its main principles and components, and describe the implementation steps and examples of good practices in educational units. The research used a literature study approach by analyzing various references on curriculum, local wisdom, Islamic educational philosophy, national education policy, and local content implementation practices. The results of the study show that the design of a local wisdom-based curriculum is based on Pancasila, the National Education System Law, and local content regulations, with the principles of contextuality, relevance, participation, integration, flexibility, and sustainability. Implementation can be realized through the integration of local values in objectives, content, learning strategies, media, and evaluation, as well as strengthening the role of teachers, schools, communities, and local governments. The main obstacles include limited teacher competence, a lack of local teaching materials, and weak policy support; therefore, it is necessary to strengthen the capacity of educators, develop local content guidelines, establish school-community partnerships, and digitize local wisdom.